1994
DOI: 10.1111/j.1600-9657.1994.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Moisture content of vital vs endodontically treated teeth

Abstract: The moisture content of vital and endodontically treated teeth was compared in matched pairs of contralateral human teeth extracted for prosthodontic reasons. Samples from each tooth were weighed then placed in an oven to remove the unbound water from the dentin. Weighing was carried out daily until a constant weight was achieved for three days. The moisture content was then calculated and expressed as a percentage of the initial sample weight. It was found that vital dentin had a moisture content of 12.35% wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
93
2
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(103 citation statements)
references
References 8 publications
0
93
2
8
Order By: Relevance
“…However, in this study, inter-individual variabilities were high, also giving higher values compared to the results of this study. Additionally, all bound water was not regarded by Papa and others, 25 which might explain the marginally lower values compared to the values from this study. As mentioned above, human dentin contains approximately 11% water, but the individual values range between 8% and 16%, depending on methodical differences.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…However, in this study, inter-individual variabilities were high, also giving higher values compared to the results of this study. Additionally, all bound water was not regarded by Papa and others, 25 which might explain the marginally lower values compared to the values from this study. As mentioned above, human dentin contains approximately 11% water, but the individual values range between 8% and 16%, depending on methodical differences.…”
Section: Discussioncontrasting
confidence: 55%
“…The overall water content of bovine dentin obtained with the applied Karl-Fischer-methodology was 15.2%. This value is slightly higher than the average outcome by Papa and others, 25 who investigated the water content of human dentin thermogravimetrically. However, in this study, inter-individual variabilities were high, also giving higher values compared to the results of this study.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…12 However, even necrotic teeth contain dentinal fluid. 13 Using the cellulose membrane technique described here, we were able to collect MMPs from teeth with necrotic teeth also (data not shown). Consequently, absorption of fluid through dentin by cellulose may be necessary to get maximum yields regardless of the condition of the pulp.…”
Section: Discussionmentioning
confidence: 99%
“…22 In the present study, the use of different rewetting solutions simulated the conditions of dentin moisture. Under in vivo conditions, the root dentin of endodontically treated teeth has a moisture level of 12.1%, 23 and this moisture is perhaps insufficient to promote the bioactivity of materials within the root canal. Reys-Carmona et al 24,25 suggested the use of PBS as intracanal medication to promote biomineralization of MTA apical plugs in the interior portion of root canals, since the biomineralization of MTA can only be achieved in direct contact with the periodontium and dentin.…”
Section: Discussionmentioning
confidence: 99%